Regulatory Capture in Banking. (IMF Working Papers; Working Paper ;, 2006)
Banks will want to influence the bank regulator to favor their interests, and they typically have the means to do so. It is shown that such "regulatory capture" in banking does not imply ineffectual regulation; a "captured" regulator may impose very tight, costly prudential requirements to reduce negative spillovers of risk-taking by weaker banks. In these circumstances, differences in the regulatory regime across jurisdictions may persist because each adapts its regulations to suit its dominant incumbent institutions.